1972
DOI: 10.2134/agronj1972.00021962006400050017x
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of Seed Protein and Amino Acid Composition to Seedling Vigor and Yield of Wheat1

Abstract: The seed of 17 phenotypes of a Mexican semidwarf wheat (Triticum aestivum L. ‘Inia 66’) was analyzed for protein and amino acid composition. These parameters were related to seedling vigor and yield to determine if amino acid composition would give a better estimate of potential vigor and yield within a genotype than seed protein. The seedling dry matter showed a high positive correlation with seed protein content (r = 0.93***). Analysis of amino acids in acid hydrolysates of the seed indicated that mole perce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
14
0
1

Year Published

1973
1973
2001
2001

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(15 citation statements)
references
References 9 publications
0
14
0
1
Order By: Relevance
“…Kaufmann and Guitard (1967) using two barley cultivars found a positive relation-ship between seed size, SV and mature plant yield. Kaufmann Ries and associates Ries 1972, 1973:, Table 4. As found in the previous experiment, the larger seeds were higher in protein content.…”
mentioning
confidence: 99%
“…Kaufmann and Guitard (1967) using two barley cultivars found a positive relation-ship between seed size, SV and mature plant yield. Kaufmann Ries and associates Ries 1972, 1973:, Table 4. As found in the previous experiment, the larger seeds were higher in protein content.…”
mentioning
confidence: 99%
“…The combination of glutamine-glutamate and proline make up as much as 40 mole % of the total amino acid composition of wheat meal. These amino acids have been shown to be positively correlated with seedling vigor (7). The sparsity of information concerning the composition and function of cereal endosperm proteins may be partly due to their insolubility in most solvents.…”
mentioning
confidence: 99%
“…Jensen (1988) and Townsend (1993) have reported seedling vigour to be influenced by seed weight and size, *Corresponding author although Jensen (1988) found that selecting for seed weight and size led to increased protein and lowered seed oil content in the resulting population. Lowe, Ayes & Ries (1972) and Evans & Bhatt (1977) found protein content to be positively correlated with seedling vigour in wheat. They suggested that the seedling vigour of the next generation can be increased either by the use of nitrogen fertiliser or by selection of large seeds.…”
Section: Introductionmentioning
confidence: 98%